Penerapan Metode Pembelajaran Whole Brain Teaching pada Materi Maple - Mohamad Khafid Irsyadi; Ayu Silvi Lisvian Sari (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2020)
This research is a Classroom Action Research which aims to describe the application of Whole Brain Teaching learning method to Maple material. The steps of the learning model are as follows: (1) Yes-Class, the lecturer observes the readiness of students in starting the lecture by saying